Dual-process theory and Investment Behaviours of South African Students - Nomlala, Bomi; Ogun, Moyosore; Chipeya, Tshegang; Latiff, Arshad Abdul (EuroEconomica, 2022)
Hitherto, the investment behaviours of university students in South Africa remains largely unknown. Understanding behavioural tendencies of students studying towards business degrees can reveal interesting facts about the mediating role of financial education on financial behaviours. The study is based on a survey of 344 business students at a South African university whose investment behaviours and the relationship between their investment behaviours and their socio-demographic factors were voluntarily assessed. As a novel study, there is currently no scientific evidence on the investment behaviours of South African, especially such considering the investment behaviour of South African students using the Dual-process theory approach. This study utilised ANOVA and a logistic regression model to analyse and explore relationships between the students’ mean percentage scores and their investment behaviours vis-à-vis their socio-demographic factors. The findings suggest that business students have negative investment behaviours as they are likely to rely on their intuition rather than the cognitive thinking process. Furthermore, it was found that students in Finance-related professions are more likely to rely on their intuition when making financial decisions in comparison to their Non-Finance related counterparts. Lastly, although it was found that there is no statistical significance between students’ demographic factors towards intuitive investment behaviour and the overall investment behaviour of students. The findings of the study suggest that male students and students who major in Law degrees are less likely to make uncontrollable, unintentional, unconscious and efficient (fast) finance-related decisions.